The trainee teacher's handbook a companion for initial teacher training - Thompson, Carol 1963-; Wolstencroft, Peter (Learning Matters, 2018)
"This book helps trainees to build skills and focus on developing their professional practice through understanding, reflection and experimentation. Its practical structure and learning features help readers to recognise their own learning needs and set their own targets"--Provided by publisher.